Actively delaying death to increase organ donation. (17th February 2012) - Watkinson, Peter; McKechnie, Stuart; Wilkinson, Dominic; Salmon, Jonathan; Young, Duncan
Abstract : New NICE guidance supports this but careful consideration should precede implementation